Sea Traffic Management (STM) in the Vessel Traffic Service (VTS) - Flodin, Teodor; Johansson, Philip (My University, 2019)
The digitalization in the shipping industry has during the last decade resulted in different research projects aiming to make the shipping chain more effective and efficient. International Maritime Organization (IMO) has developed a “Strategy Implementation Plan” to help navigate the development in the right direction with demands which the projects are trying to fulfil. One of the projects is Sea Traffic Management (STM) which has developed tools to help assist with decision making and a more efficient way of navigating and planning voyages. The tools are aimed towards the mariners on board but also the operators ashore in the Vessel Traffic Service (VTS). The aim of this thesis is to get an understanding of what the Vessel Traffic Service Operators (VTSO) think of the STM tools user interface/friendliness, their benefits, and what potential problems they could produce. The results are supported by answers from a questionnaire collected during full scale simulation testing of the STM services. This helped to gain a brief understanding in their thought of the STM tools and how user friendly the tools are. The results were strengthened by four interviews of VTSOs who participated in the simulation runs and the questionnaire to get a deeper understanding of the pros and cons on the STM tools. The result indicated that the tools were over-all user friendly and was to a benefit for the VTSOs with increased foresight and overview.
Keywords: VTS, VTSO, IMO, user friendliness, shipping, STM, Sea Traffic Management